Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Jiang, Yan (Zhejiang University Press, 2013)

(untitled)
Busulfan/cyclophosphamide (Bu/Cy) conditioning regimen has been widely used to treat cancer patients, while their effects on major internal organs in females are not fully understood. We treated female mice with Bu/Cy, and examined the histopathology of major internal organs on Day 30 after the treatment. The results show that Bu/Cy treatment affected the ovaries most extensively, while it had less effect on the spleen, lungs, and kidneys, and no effect on the heart, liver, stomach, and pancreas. To better understand the effect of Bu/Cy on the ovaries, we counted follicles, and determined the levels of ovarian steroids. The Bu/Cy-treated mice showed a reduction of primordial and primary follicles (P<0.01) on Day 30 and a marked loss of follicles at all developmental stages (P<0.01) on Day 60. Plasma levels of estradiol and progesterone in Bu/Cy-treated mice decreased by 43.9% and 61.4%, respectively. Thus, there was a gradual process of follicle loss and low estradiol in Bu/Cy-treated mice; this is a profile similar to what is found in women with premature ovarian failure (POF). The Bu/Cy-treated mice may serve as a useful animal model to study the dynamics of follicle loss in women undergoing POF.